Exploring English Teachers' Difficulties in Teaching Speaking - Rezeki, Putri; Dalimunte, Muhammad (Institut Agama Islam Negeri Parepare, 2024)
Speaking is an essential part of mastering any language, including English. However, teaching speaking often poses various difficulties and obstacles for teachers. This research aimed to investigate the difficulties English teachers face when teaching speaking skills in the classroom. The study utilized a qualitative case study approach, collecting data through semi-structured interviews and questionnaires with eight teacher participants who all taught the same grade level at different schools. The findings revealed five major difficulties: 1) teachers' lack of vocabulary; 2) students' lack of motivation and student anxiety; 3) insufficient school facilities and equipment; 4) curriculum used. This shows that problems arise from multiple factors, not just one, and solutions are needed to minimize these difficulties.